Pengaruh Profitabilitas, Struktur Aktiva, Dan Dividen Terhadap Rasio Hutang Dan Harga Saham Perusahaan Yang Terdaftar Di JII Periode 2010-2014 - Fina Rahmi Mauluda; Leo Herlambang (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
The purpose of this research is to determine the direct effects and indirect effects of profitability,asset structure, and dividen to stock price from debt ratio in Jakarta Islamic Index periode 2010-2014. The approach research used are quantitative with multiple linear regression analysis and path analysis technique. T test results stated that the ROA has a positive significant effect and DPR has a negative significant on DER with direct effects 53% and 38%. While assets structure has a negative not significant effect on DER with 5% direct effect. Than, ROA has positive significant effect and assets structure has a negative significant on stock price with direct effects 33,5% and 13,7%. DPR and DER have positive not significant effects on stock price with direct effects 3,1 and 4,1%. Amount of indirect effect of ROA, assets structure and DPR on stock price from DER are 2,173%, 0,25% and 1,56%.